Reduced Plasma Levels of 25-Hydroxycholesterol and Increased Cerebrospinal Fluid Levels of Bile Acid Precursors in Multiple Sclerosis Patients - William Griffiths (Molecular Neurobiology, 2016)
Multiple sclerosis (MS) is an autoimmune, inflammatory disease of the central nervous system (CNS). We have measured the levels of over 20 non-esterified sterols in plasma and cerebrospinal fluid (CSF) from patients suffering from MS, inflammatory CNS disease, neurodegenerative disease and control patients. Analysis was performed following enzyme-assisted derivatisation by liquid chromatography-mass spectrometry (LC-MS) exploiting multistage fragmentation (MS n ). We found increased concentrations of bile acid precursors in CSF from each of the disease states and that patients with inflammatory CNS disease classified as suspected autoimmune disease or of unknown aetiology also showed elevated concentrations of 25-hydroxycholestertol (25-HC, P < 0.05) in CSF. Cholesterol concentrations in CSF were not changed except for patients diagnosed with amyotrophic lateral sclerosis (P < 0.01) or pathogen-based infections of the CNS (P < 0.05) where they were elevated. In plasma, we found that 25-HC (P < 0.01), (25R)26-hydroxycholesterol ((25R)26-HC, P < 0.05) and 7α-hydroxy-3-oxocholest-4-enoic acid (7αH,3O-CA, P < 0.05) were reduced in relapsing-remitting MS (RRMS) patients compared to controls. The pattern of reduced plasma levels of 25-HC, (25R)26-HC and 7αH,3O-CA was unique to RRMS. In summary, in plasma, we find that the concentration of 25-HC in RRMS patients is significantly lower than in controls. This is consistent with the hypothesis that a lower propensity of macrophages to synthesise 25-HC will result in reduced negative feedback by 25-HC on IL-1 family cytokine production and exacerbated MS. In CSF, we find that the dominating metabolites reflect the acidic pathway of bile acid biosynthesis and the elevated levels of these in CNS disease is likely to reflect cholesterol release as a result of demyelination or neuronal death. 25-HC is elevated in patients with inflammatory CNS disease probably as a consequence of up-regulation of the type 1 interferon-stimulated gene cholesterol 25-hydroxylase in macrophages